Peran Media Sosial Dalam Memoderasi Religiusitas Terhadap Perilaku Konsumsi Muslim Gen-Z Pada Boikot Produk Israel - Nur Azizah Hasanah; Madnasir; Nurlaili (DPPM Universitas Pelita Bangsa, 2026)
The purpose of this study is to analyze the influence of religiosity on Muslim consumption behavior, as well as the role of social media as a moderating variable. An associative quantitative method was used with a sample of 150 Gen-Z respondents in Bandar Lampung City. Data analysis was performed using SEM-PLS to test the outer and inner models. The results show that religiosity has a significant positive effect on consumption behavior. Meanwhile, social media does not have a significant moderating effect on the relationship between variables. Therefore, Gen-Z consumption patterns pay more attention to religious commitment than social media information. Implicitly, this emphasizes the importance of religiosity as an effective strategy in Muslim consumption behavior, thereby contributing to the development of sharia economic theory and value-based education and business practices.